Behavior of juvenile lizards (Iguana iguana) in a conflict between temperature regulation and palatable food - Balasko, M; Cabanac, M (Brain, behavior and evolution, 1998)
Juvenile green iguanas were placed in a situation of conflict between two motivations: a thermoregulatory drive and the attraction of a palatable bait. To be able to reach the bait (lettuce), they had to leave a warm refuge, provided with standard food, and venture into a cold environment. In experiment 1 the time interval between sessions with bait, ranging from 1 to 8 days, had no effect on the duration of stay on the bait. This result shows that the lettuce was not a necessary food, deprivation of which would have had to be compensated for. In experiment 2 as the ambient temperature at the bait decreased the lizards spent less time feeding on lettuce, and they visited the bait less frequently. This result shows that the lizards traded off the palatability of the bait with the disadvantage of the cold. These findings support the hypothesis that a common currency makes it possible for lizards to compare two sensory modalities.